Literature: Comparison Financial Literacy In The World Milenial VS Gen Z - Etty Sri Wahyuni; Putri Mauliza; Sri Yanti (Digital Innovation : International Journal of Management, 2024)
This study provides a comprehensive comparative analysis of financial literacy among Millennials and Generation Z across various global contexts, drawing on recent data from major international surveys. The research examines key indicators of financial knowledge, behaviors, and attitudes, revealing a complex landscape characterized by both promising developments and significant challenges. While both generations demonstrate increased engagement with digital financial services, there often remains a gap between their technological savviness and comprehensive financial understanding. The analysis highlights significant regional disparities in financial literacy, influenced by factors such as digital technology prevalence, education systems, economic environments, and cultural attitudes. The study underscores the profound impact of technology on financial literacy and emphasizes the need for tailored financial education incorporating digital literacy and critical thinking skills. Policy implications include developing comprehensive national strategies for financial literacy and fostering international cooperation. This research contributes valuable insights for educators, policymakers, and financial institutions to enhance financial capability among young adults globally in an increasingly complex financial landscape.